(untitled) (World Bulletin of Social Sciences, 2025)
An artistic image is also clearly distinguished from any other creative work by its emotional content, which has a certain emotional-aesthetic ideological impact” 1 . Since an artistic idea is expressed through images, only if the writer succeeds in choosing a hero who is in line with the spirit of the work and artistically embodies him, that hero will achieve artistic perfection. Since an artistic image carries the author’s aesthetic ideal in the work, its selection in accordance with the purpose depends on the writer’s skill. Especially when writing a work on a historical topic, choosing a hero is a responsible task for him, which requires the writer to thoroughly study the specific period related to the topic he has chosen, as well as sources about historical figures. In such a situation, the writer is required to strictly adhere to the criteria of historicity and artistry